2014
DOI: 10.1186/1746-4811-10-5
|View full text |Cite
|
Sign up to set email alerts
|

EMS mutagenesis in mature seed-derived rice calli as a new method for rapidly obtaining TILLING mutant populations

Abstract: BackgroundTILLING (Targeting Induced Local Lesions IN Genomes) is a reverse genetic method that combines chemical mutagenesis with high-throughput genome-wide screening for point mutation detection in genes of interest. However, this mutation discovery approach faces a particular problem which is how to obtain a mutant population with a sufficiently high mutation density. Furthermore, plant mutagenesis protocols require two successive generations (M1, M2) for mutation fixation to occur before the analysis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 60 publications
4
73
0
2
Order By: Relevance
“…Thus, mutagenesis can affect the percent germination (Serrat et al, 2014). As shown in Figure 1, a significant reduction in seed germination was observed with increasing EMS concentrations (P ≤ 0.05).…”
Section: Germination Percentage (Gp) and Ld 50mentioning
confidence: 83%
See 2 more Smart Citations
“…Thus, mutagenesis can affect the percent germination (Serrat et al, 2014). As shown in Figure 1, a significant reduction in seed germination was observed with increasing EMS concentrations (P ≤ 0.05).…”
Section: Germination Percentage (Gp) and Ld 50mentioning
confidence: 83%
“…That may be due to the use of different presoaking treatments before EMS treatment, which may affect the quantity of EMS absorbed by the germinating embryo. Injury is also dependent on the quantity of EMS that reaches the meristematic region where the germ cells are contained (Serrat et al, 2014). In cotton plants, Aslam et al (2013) observed that the percent of injury increased with increasing EMS concentration.…”
Section: Injury Percent (Ip)mentioning
confidence: 99%
See 1 more Smart Citation
“…Mutation induction assists breeding programs by increasing variability and therefore obtaining genotypes with agronomically important traits, more adapted to different environmental conditions (Serrat et al 2014). The spontaneous mutation rate in higher plants is very low, ranging from about 10 −5 to 10 −8 (Jiang and Ramachandran 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Mutagenesis provides a powerful technique to improve plant breeding and assist functional and genomic analyses of crop plants. This technique was first introduced with the use of x-ray and radium radiations followed by fast neutron and gamma radiation (Serrat et al, 2014). Because such application of physical mutagens required specialized equipment, chemical mutagens were introduced later.…”
Section: Introductionmentioning
confidence: 99%